The Antibiotic Guardian campaign: a qualitative evaluation of an online pledge-based system focused on making better use of antibiotics - Joanna May Kesten; Alex Bhattacharya; Diane Ashiru-Oredope; Maya Gobin; Suzanne Audrey (BMC, 2017)
Abstract Background The Antibiotic Guardian Campaign was developed to increase commitment to reducing Antimicrobial Resistance (AMR), change behaviour and increase knowledge through an online pledge system for healthcare professionals and members of the public to become Antibiotic Guardians (AG). This qualitative evaluation aimed to understand AG experiences of the campaign and perceived impact on behaviour. Methods Ninety-four AGs (48 via a survey and 46 who had agreed to future contact) were invited to participate in a telephone semi-structured interview. The sample was based on self-identification as a healthcare professional or a member of the public, pledge group (e.g. adults, primary care prescribers etc.), pledge and gender. Interviews explored how participants became aware of the campaign, reasons for joining, pledge choices, responses to joining and views about the campaign's implementation. Interviews were analysed using the Framework Method. Results Twenty-two AGs (10 healthcare professionals and 12 members of the public) were interviewed. AGs became aware of the campaign through professional networks and social media, and were motivated to join by personal and professional concern for AMR. Choice of pledge group and pledge were attributed to relevance and potential impact on AMR and the behaviour of others through pledge enactment and promotion of the campaign. Most AGs could not recall their pledge unprompted. Most felt they fulfilled their pledge, although this reflected either behaviour change or the pledge reinforcing pre-existing behaviour. The campaign triggered AGs to reflect on AMR related behaviour and reinforced pre-existing beliefs. Several AGs promoted the campaign to others. Responding collectively as part of the campaign was thought to have a greater impact than individual action. However, limited campaign visibility was observed and the campaign was perceived to have restricted ability to reach those unaware of AMR. Conclusions AGs were motivated to reduce AMR and most felt they fulfilled their pledges although for many this appeared to be through reinforcement of existing behaviours. We recommend that the campaign engages those without pre-existing knowledge of AMR by increasing its visibility, capitalising on the diffusion of its message and including more awareness-raising content for those with limited AMR knowledge.